2003
DOI: 10.1046/j.1365-2036.2003.01588.x
|View full text |Cite
|
Sign up to set email alerts
|

The burden of illness of gastro‐oesophageal reflux disease: impact on work productivity

Abstract: Summary Background:  The impact of gastro‐oesophageal reflux disease on work productivity has become increasingly important, as the symptoms of gastro‐oesophageal reflux disease affect individuals in their productive years of life. Aims:  To assess the impact of gastro‐oesophageal reflux disease on reduced work productivity and to identify the predictors of reduced productivity. Methods:  A sample of employed individuals reporting chronic heartburn was selected from US household mail survey respondents. Heartb… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

7
113
0
8

Year Published

2006
2006
2022
2022

Publication Types

Select...
5
3
1

Relationship

0
9

Authors

Journals

citations
Cited by 147 publications
(128 citation statements)
references
References 30 publications
7
113
0
8
Order By: Relevance
“…Furthermore, this treatment was more eff ective in reducing the number of work hours missed due to GERD-related sleep disturbances. Th ese results are not unexpected when one considers the connection between repeated lack of sleep during the night and daytime sleepiness ( 9 ), as well as reduced HRQoL and work productivity ( 11 negative impact of nocturnal GERD on HRQoL and work productivity is well recognized ( 7,8,10 ). A recent survey of over 600 GERD patients on various PPI therapies found that the majority of patients continued to experience heartburn, with 83 % experiencing nocturnal symptoms and almost a quarter of these patients reporting severe or very severe nocturnal symptoms ( 32 ).…”
Section: Esophagusmentioning
confidence: 89%
See 1 more Smart Citation
“…Furthermore, this treatment was more eff ective in reducing the number of work hours missed due to GERD-related sleep disturbances. Th ese results are not unexpected when one considers the connection between repeated lack of sleep during the night and daytime sleepiness ( 9 ), as well as reduced HRQoL and work productivity ( 11 negative impact of nocturnal GERD on HRQoL and work productivity is well recognized ( 7,8,10 ). A recent survey of over 600 GERD patients on various PPI therapies found that the majority of patients continued to experience heartburn, with 83 % experiencing nocturnal symptoms and almost a quarter of these patients reporting severe or very severe nocturnal symptoms ( 32 ).…”
Section: Esophagusmentioning
confidence: 89%
“…Among those reporting GERD symptoms, up to 89 % report nocturnal symptoms ( 1,4 -6 ), resulting in impairment in health-related quality of life (HRQoL) and signifi cantly worse sleep quality ( 7,8 ). Because continued sleep disruption leads to increased daytime sleepiness ( 9 ), nocturnal heartburn can reduce productivity while patients are present at work, as well as reduce function when performing normal daily activities ( 7,8,10,11 ). Th e continued presence of nocturnal heartburn despite routine medical treatment is strongly associated with decreases in HRQoL ( 12 ).…”
mentioning
confidence: 99%
“…GERD is associated with a negative impact on health-related quality of life (HRQL), increased risk of esophageal adenocarcinoma, and great costs for patients and society [3][4][5][6][7][8] . Established risk factors for GERD are overweight, tobacco smoking, low socioeconomic status, and heredity [9][10][11][12][13][14][15] , while the potential role of physical activity is complex and intriguing.…”
Section: Introductionmentioning
confidence: 99%
“…9 Reduced daytime productivity, both at and outside work, whether due to sleep disturbances or reflux during the day also notably affects patients' daily living. 10,11 Consequently, impact of different GERD therapies on HRQoL is important in assessing treatment outcome, primarily to improve medical therapy. However, Prasad et al 7 only found 15 articles that looked on the impact of treatment on quality of life among nearly 1000 published on GERD treatment.…”
Section: Introductionmentioning
confidence: 99%